Sir Leonard Parsons of Birmingham (1879–1950) and antenatal paediatrics. Issue 1 (1st January 2002) - Dunn, P M
Abstract : Born and educated in the Midlands, Sir Leonard Parsons made major contributions to the field of paediatrics in that area and played a leading role in the regional organisation of this specialty throughout the United Kingdom in the later years of his life. He was a founder member and later President of the British Paediatric Association, and later became Vice-President of the International Pediatric Congress and the President of the paediatric section of the Royal Society of Medicine.